Albert Payson Terhune papers - Terhune, Albert Payson, 1872-1942.
Correspondence, addresses, literary manuscripts, articles, radio scripts, clippings, scrapbooks, and other papers. Consists primarily of manuscripts for Terhune's short stories and articles which relate chiefly to dogs. Other topics include boxing and his travels in the Middle East. Includes copies of articles by Joseph T. Scarry and biographical sketches of Terhune by John F. Trow and Terhune's wife, Anice Terhune. Correspondents include Hester Bird, Jacques Chambrun, Bruce Chapman, Nannine Joseph, Sinclair Lewis, Robert Welles Ritchie, and Joseph T. Scarry.
Author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bird, Hester -- Correspondence; Chambrun, Jacques -- Correspondence; Chapman, Bruce, -- 1900- -- Correspondence; Joseph, Nannine -- Correspondence; Lewis, Sinclair, -- 1885-1951 -- Correspondence; Ritchie, Robert Welles, -- 1879-1942 -- Correspondence; Scarry, Joseph T; Scarry, Joseph T. -- Correspondence; Terhune, Anice, -- 1873-1964.; Trow, John F; Dogs; Boxing; Radio scripts; Short stories, American; Middle East -- Description and travel; Authors